MAPK/ERK signaling in activated T cells inhibits CD95/Fas-mediated apoptosis downstream of DISC assembly - Holmström, Tim; Krammer, Peter H. (The EMBO journal, 2000)
When T cells are activated, the expression of the CD95 ligand is elevated, with the purpose of inducing apoptosis in target cells and to later eliminate the activated T cells. We have shown previously that mitogen-activated protein kinase (MAPK or ERK) signaling suppresses CD95-mediated apoptosis in different cellular systems. In this study we examined whether MAPK signaling controls the persistence and CD95-mediated termination of an immune response in activated T cells. Our results show that activation of Jurkat T cells through the T cell receptor immediately suppresses CD95-mediated apoptosis, and that this suppression is mediated by MAPK activation. During the phase of elevated MAPK activity, the activation of caspase-8 and Bid is inhibited, whereas the assembly of a functional death-inducing signaling complex (DISC) is not affected. These results explain the resistance to CD95 responses observed during the early phase of T cell activation and suggest that MAPK-activation deflects DISC signaling from activating caspase-8 and Bid. The physiological relevance of the results was confirmed in activated primary peripheral T cells, in which inhibition of MAPK signaling markedly sensitized the cells to CD95-mediated apoptosis.